2022
DOI: 10.1177/24741264221120490
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Macular Holes With Topical Therapy

Abstract: Purpose: To report the results of a nonsurgical approach to repair macular holes (MHs). Methods: A retrospective chart review of consecutive patients with MHs from 2018 to 2021 was performed. Topical therapy consisted of a steroidal agent, a nonsteroidal agent, and a carbonic anhydrase inhibitor. Data collected included the size, stage, and duration of the MH; topical agents used and the duration; lens status; and complications. Macular edema was graded on a scale ranging from 0 (no edema) to 4 (large amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Forty-nine studies had complete data with a total of 181 eyes forming the basis of our analysis [Table 2]. [ 18 ][ 19 ][ 20 ][ 21 ][ 22 ][ 23 ][ 24 ][ 25 , 26 , 27 , 28 ][ 29 ][ 30 ][ 31 ][ 32 ][ 33 ][ 34 ][ 35 ][ 36 ][ 37 ][ 38 ][ 39 ][ 40 ][ 41 ][ 42 ][ 43 ][ 44 ][ 45 ][ 46 ][ 47 ][ 48 ][ 49 ][ 50 ][ 51 ][ 52 ][ 53 ][ 54 ][ 55 ][ 56 ] Mean vision improved significantly ( P 0.005) from 20/65 to 20/41 over a mean follow-up of two years. The median diameter of IFTMH was 166 with 81.1% being categorized as small holes.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine studies had complete data with a total of 181 eyes forming the basis of our analysis [Table 2]. [ 18 ][ 19 ][ 20 ][ 21 ][ 22 ][ 23 ][ 24 ][ 25 , 26 , 27 , 28 ][ 29 ][ 30 ][ 31 ][ 32 ][ 33 ][ 34 ][ 35 ][ 36 ][ 37 ][ 38 ][ 39 ][ 40 ][ 41 ][ 42 ][ 43 ][ 44 ][ 45 ][ 46 ][ 47 ][ 48 ][ 49 ][ 50 ][ 51 ][ 52 ][ 53 ][ 54 ][ 55 ][ 56 ] Mean vision improved significantly ( P 0.005) from 20/65 to 20/41 over a mean follow-up of two years. The median diameter of IFTMH was 166 with 81.1% being categorized as small holes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported cases of FTMH closure after treatment with topical steroids and NSAIDs, with most holes having elevated, edematous edges and with the presence of intraretinal cystoid spaces, suggesting an inflammatory trigger as the causative failure mechanism. 16 20 A recent study by Bonnell et al 18 described for the first time the use of a dexamethasone implant for the treatment of an FTMH. 21 The authors presented the case of a 79-year-old man presenting with a small (134 µm) FTMH that initially closed with steroids and NSAIDs but reopened after the medication was tapered.…”
Section: Discussionmentioning
confidence: 99%